Longitudinal trajectories of blood lipid levels in an ageing population sample of Russian Western-Siberian urban population - Hubacek, Jaroslav A; Nikitin, Yuri; Ragino, Yulia; Stakhneva, Ekaterina; Pikhart, Hynek; Peasey, Anne; Holmes, Michael V; Stefler, Denes; Ryabikov, Andrey; Verevkin, Eugeny; Bobak, Martin; Malyutina, Sofia (PloS one, 2021)
This study investigated 12-year blood lipid trajectories and whether these trajectories are modified by smoking and lipid lowering treatment in older Russians. To do so, we analysed data on 9,218 Russian West-Siberian Caucasians aged 45-69 years at baseline participating in the international HAPIEE cohort study. Mixed-effect multilevel models were used to estimate individual level lipid trajectories across the baseline and two follow-up examinations (16,445 separate measurements over 12 years). In all age groups, we observed a reduction in serum total cholesterol (TC), LDL-C and non-HDL-C over time even after adjusting for sex, statin treatment, hypertension, diabetes, social factors and mortality (P<0.01). In contrast, serum triglyceride (TG) values increased over time in younger age groups, reached a plateau and decreased in older age groups (> 60 years at baseline). In smokers, TC, LDL-C, non-HDL-C and TG decreased less markedly than in non-smokers, while HDL-C decreased more rapidly while the LDL-C/HDL-C ratio increased. In subjects treated with lipid-lowering drugs, TC, LDL-C and non-HDL-C decreased more markedly and HDL-C less markedly than in untreated subjects while TG and LDL-C/HDL-C remained stable or increased in treatment naïve subjects. We conclude, that in this ageing population we observed marked changes in blood lipids over a 12 year follow up, with decreasing trajectories of TC, LDL-C and non-HDL-C and mixed trajectories of TG. The findings suggest that monitoring of age-related trajectories in blood lipids may improve prediction of CVD risk beyond single measurements.
Keywords: Triglycerides; Cholesterol, HDL; Cholesterol, LDL; Humans; městské obyvatelstvo; Longitudinal Studies; lidé středního věku; Female; Aged; stárnutí; lipidy; senioři; lidé; Aging; LDL-cholesterol; triglyceridy; ženské pohlaví; longitudinální studie; Male; Middle Aged; HDL-cholesterol; Rusko; Lipids; Russia; Smoking; mužské pohlaví; kouření; Urban Population